Systematic literature review on designing trust-based security for WSNs - Raja waseem Anwar; Anazida Zainal; Saleem Iqbal (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The study assessed the design and development of trust-based security for wireless sensor networks. A qualitative approach was opted by employing systematic review analysis, which was assessed using secondary data collection. The design and development of trust-based security were mainly targeted, and 140 publications were randomly reviewed, from which 24 studies were finalized after excluding irrelevant data and studies that only contained abstracts. The results were analyzed focusing on the designs, applications and protocols and trust factors. Different studies have been evaluated, which have suggested that proper design and development of trust-based security should be the foremost aim to be applied in user environments. The study suggested that designing the trust management models based on the taxonomy of routing applications and relevant algorithms could be a part of future investigations.